The integrative effects of behavior and morphology on amphibian movement. Issue 3 (15th January 2019) - Bredeweg, Evan M.; Morzillo, Anita T.; Thurman, Lindsey L.; Garcia, Tiffany S.
Abstract: Animal movement and dispersal are key factors in population dynamics and support complex ecosystem processes like cross‐boundary subsidies. Juvenile dispersal is an important mechanism for many species and often involves navigation in unfamiliar habitats. For species that metamorphose, such as amphibians, this transition from aquatic to terrestrial environments involves the growth and use of new morphological traits (e.g., legs). These traits strongly impact the fundamental ability of an organism to move in novel landscapes, but innate behaviors can regulate choices that result in the realized movements expressed. By assessing the integrative role of morphology and behavior, we can improve our understanding of juvenile movement, particularly in understudied organisms like amphibians. We assessed the roles of morphological (snout‐vent length and relative leg length) and performance (maximal jump distance) traits in shaping the free movement paths, measured through fluorescent powder tracking, in three anuran species, Pacific treefrog ( Hyliola regilla ), Western toad ( Anaxyrus boreas ), and Cascades frog ( Rana cascadae ). We standardized the measurement of these traits to compare the relative role of species' innate differences versus physical traits in shaping movement. Innate differences, captured by species identity, were the most significant factor influencing movement paths via total movement distance and path sinuosity. Relative leg length was an important contributor but significantly interacted with species identity. Maximal jump performance, which was significantly predicted by morphological traits, was not an important factor in movement behavior relative to species identity. The importance of species identity and associated behavioral differences in realized movement provide evidence for inherent species differences being central to the dispersal and movement of these species. This behavior may stem from niche partitioning of these sympatric species, yet it also calls into question assumptions generalizing anuran movement behavior. These species‐level effects are important in framing differences as past research is applied in management planning. Abstract : Species‐specific behavior is central in shaping the movement patterns of juvenile amphibians. Juvenile frogs and toads must navigate new terrestrial habitats upon emerging from ponds after metamorphosis. Past work has focused on how characteristics of an individual's body may change their ability to move. We found that movement ability of three co‐occurring species was not captured by physical ability alone, but was strongly tied to species identity.